STUDYING THE RELATIONSHIP MODEL ONLINE CONSUMER REVIEW TOWARDS CONSUMER PURCHASE INTENTION ON SOCIAL COMMERCE PLATFORMS: EVIDENCE IN INDONESIA - Septiani, Emilia; Farida, Farida; Syarifa Diah Kusuma, Rr. Chusnu; Anggraini, Raden Isma; Zaki, Nur Amalina Mohamad (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
This research examines the influence of electronic word of mouth (e-WOM), viral marketing, and online consumer reviews on purchase intention on social commerce platforms. The research uses a quantitative approach with a survey method distributed to active social commerce users in Indonesia, and the data obtained is analyzed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique. The research results show that the e-WOM and viral marketing variables positively and significantly affect purchase intention. In contrast, online consumer reviews have a positive but not significant effect. These findings indicate that digital social interactions and the spread of viral content have a dominant role in influencing consumer purchasing intentions, while consumer reviews have not been able to become a strong determining factor in purchasing decisions. This research provides theoretical contributions by enriching the literature on consumer behaviour in social commerce and practical implications for business people to maximise digital marketing strategies based on social interaction and viral content, accompanied by managing consumer reviews that remain relevant in maintaining brand trust..